The Relationship and Factors The Parenting Style of Parents Who Married Early with The Development of Children Aged 1-5 Years - Faza Nabila; Ariani Ariani; Safrina Dewi Ratnaningrum (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Early marriage is a major problem in the process of child rearing. Improper parenting patterns can hinder the growth and development of children. This study aims to analyze the relationship and factors that influence the parenting style of parents who marry early on the development of children aged 1 to 5 years in the Tulungagung district. Material and Methods: Research using cross-sectional analitic observation, a sample of 203 respondents who were married under 19 years of age in 2017-2021 and had children aged 1-5 years using a questionnaire and Denver II. Statistical analysis calculation using chi-square and path analysis. Results: The chi-square test results showed a significant relationship between the parenting style of parents who early marriage and the development of children aged 1-5 years (p<0.05). Path analysis showed that there is an influence of the parenting style of parents who early marriage on the development of children through education and number of children (p<0.05). while in terms of occupation, income, and family support, there is no influence of the parenting style of parents who early marriage on the development of children (p>0.05). Conclusion: Parents who marry early tend to adopt an authoritarian parenting style, which can lead to poor child development. Authoritarian parenting styles have low levels of democracy and parental affection. High achievement demands on children are not matched by parental love so that it makes children feel depressed.